PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP KINERJA PERUSAHAAN - Zulhaimi, Hanifa (Jurnal Riset Akuntansi dan Keuangan, 2015)
The purpose of this research is to analyze the implementation of green accounting and to find an impact of application of green accounting toward earning and stock price growth in Indonesian Industri. Industri activities oftentimes give some bad impact to environment surroundings such as natural devastation and the changes of culture, social and economic. Green accounting is a realization of corporate social responsibility to relieve the impact. The implementation of green accounting can give good image for the company however preliminary research found not many companies are implementing green accounting. This research will use quantitave approach and different test orÂ  paired T-test will use for statistical testing, in order to test the research assumptions. Variable of this research are Green accounting, Earning per Shares and Stock Price Growth. This research is expected will contribute for the development of green accounting theory and enhancement of the implementation of green accounting especially in Indonesian Industri on Asian Economic community era.